1998
DOI: 10.1103/physrevlett.81.2096
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Be (0001) Surface Thermal Expansion

Abstract: We present a first-principles study, within the quasiharmonic approximation, of the thermal expansion of Be (0001) surface. The free energy is obtained from full vibrational dispersions computed by density-functional perturbation theory. Our calculation describes very well the thermal expansion in the bulk and has been checked against first-principles molecular dynamics simulations in the surface case. We do not find the large thermal expansion recently observed experimentally and we argue that the morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 30 publications
5
30
0
Order By: Relevance
“…[3][4][5] However, extensive efforts to quantitatively explain these experimental results have not led to a consensus on a correct theoretical description. [6][7][8][9][10] Recently, a medium-energy ion-scattering ͑MEIS͒ study of Ag͑111͒ 3 reported an unexpectedly large high-temperature surface thermal expansion, where the relaxation of the first interlayer spacing, ⌬ 12 ϭ͓(d 12 Ϫd)/d͔, was observed to increase from Ϫ2.5%, its value at temperatures between 300 and 670 K, to ϩ10% at Tϭ1100 K. Here, d 12 is the separation between the first and the second atomic layers at the surface and d is the interlayer spacing in the bulk crystal. Such dramatic structural changes, unanticipated for the close-packed ͑111͒ surface, 11 have attracted considerable theoretical interest.…”
mentioning
confidence: 99%
“…[3][4][5] However, extensive efforts to quantitatively explain these experimental results have not led to a consensus on a correct theoretical description. [6][7][8][9][10] Recently, a medium-energy ion-scattering ͑MEIS͒ study of Ag͑111͒ 3 reported an unexpectedly large high-temperature surface thermal expansion, where the relaxation of the first interlayer spacing, ⌬ 12 ϭ͓(d 12 Ϫd)/d͔, was observed to increase from Ϫ2.5%, its value at temperatures between 300 and 670 K, to ϩ10% at Tϭ1100 K. Here, d 12 is the separation between the first and the second atomic layers at the surface and d is the interlayer spacing in the bulk crystal. Such dramatic structural changes, unanticipated for the close-packed ͑111͒ surface, 11 have attracted considerable theoretical interest.…”
mentioning
confidence: 99%
“…For many years, DFT has been used to calculate the phonon spectra of perfect crystals [2], and it is only a short step from that to the calculation of free energies and other thermodynamic quantities in the harmonic approximation. There have already been several reports of DFT calculations of high-temperature crystal thermodynamics [3,4,5,6,7,8,9], including solid-solid phase equilibria [10,11,12,13] using this approach. For liquids, ab initio thermodynamics first became possible with the Car-Parrinello technique [14] of DFT molecular dynamics simulation, which immediately gave a way to calculate such quantities as pressure, internal energy and temperature of a liquid in thermal equlibrium.…”
Section: Introductionmentioning
confidence: 99%
“…There has been particular attention to the thermodynamics of crystals, whose harmonic free energy can be obtained from phonon frequencies computed by standard DFT methods [5][6][7][8][9][10][11]. The ab initio treatment of liquid-state thermodynamics is also important, and thermodynamic integration has been shown to be an effective way of calculating the DFT free energy of liquids [1,3,4].…”
Section: Introductionmentioning
confidence: 99%